THE PROCESS OF TRANSITION FROM INSTITUTIONAL TO COMMUNITY-BASED SERVICES IN THE SYSTEM OF SOCIAL SERVICES IN SLOVAKIA - Vansač, P.; Novotná, A. (Україна. Здоров’я нації, 2023)
Through research on selected employees of social services establishments established by the Prešov Region, we found that the process of deinstitutionalisation has a positive impact on motivation, education, working atmosphere and communication of employees. Another aspect examined was the individual approach to the recipients of social services. Our research found that although most employees try to apply an individual approach to the recipients of social services in the social services establishment, there is still room for improvement in cooperation with the family and in designing an individual plan for the recipient of social services.